Social, Cultural, and Ecological Systems' Influence on Community Health and Wellbeing. - Newell, Sarah (2018)
An individual’s health is influenced by more than just the health care system, but also in large part by the social determinants of health. People exist within broader social, cultural, and ecological systems which influence their health outcomes through the social determinants of health. This doctoral dissertation examines social, cultural, and ecological systems to understand several factors that support and hinder community health and wellbeing to inform future policy. This dissertation incorporates a mix of methodological approaches across four interrelated research studies to better understand direct and indirect factors influencing community health and wellbeing. In doing so, this thesis is divided into four research chapters. Study 1 consists of a community-based research project that examines how food security, cultural continuity, and community health and wellbeing are connected through the sharing of harvested country food in Chesterfield Inlet, Nunavut, Canada. Based on this understanding we can demonstrate how climate change and increased shipping along the inlet affects the community as a result of changes in marine mammals and harvesting activities. Study 2 presents a logistic regression that models how cultural continuity variables impact self-rated health for participants living in Inuit Nunangat in Canada. This model uses the Arctic Supplement questions of the Aboriginal Peoples Survey to compare measures of cultural continuity to traditional measures based on government services. This study demonstrates an important link between cultural continuity and self-rated health for Inuit living in Inuit Nunangat. iv Study 3 contains a case study of different implementation successes and challenges of Locally Managed Marine Areas globally. These cases are used to understand how community member involvement as stakeholders in marine resource decision-making not only aligns with existing local and Indigenous ways of management, but also can enhance biodiversity as well as local livelihoods. Finally, Study ...